Comparative Evaluation of Clove Extract and Green-Synthesized Selenium Oxide Nanoparticles for Protection Against UV-B Induced DNA Damage: A Comet Assay-Based Study - Kawther Y. Mashjal; Hussain S. Hasan; Labeeb Ahmed Alzubaidi; Kawther Y. Mashjal; Hussain S. Hasan; Labeeb Ahmed Alzubaidi (Jurnal MIPA dan Pembelajarannya, 2026)
Ultraviolet (UV) radiation is one of the major environmental factors which can be harmful for cellular DNA. It can lead to genetic mutations and damage to DNA, which can increase the risk of a variety of diseases, including cancer. The objective of the present study was to evaluate the therapeutic effects of clove extract (Syzygium aromaticum), clove-mediated selenium nanoparticles (SeNPs) and clove extract alone on UVB-induced DNA damage in mice.  UVB exposure resulted in a significant increase in DNA damage as measured by the Olive Tail Moment in the Comet assay. Post-treatment with clove extracts reduced DNA damage however, the clove mediated selenium nanoparticles showed a stronger therapeutic effect. The SeNP-treated groups, especially after 15 min exposure, showed the lowest Olive Tail Moment values, indicating a significant reduction in genotoxicity. This suggests that clove mediated selenium nanoparticles have great therapeutic potential in repairing UV induced DNA damage and improving genome stability.